Dietary consumption of lipids as a potential risk factor for non-communicable diseases in Western Siberia - D. V. Turchaninov; N. G. Shirlina; I. A. Viktorova; V. L. Stasenko; A. D. Chubarova; E. A. Vilms (Фундаментальная и клиническая медицина)
Aim. To assess the profile of lipid consumption in the population of Omsk Region, located in Western Siberia.Materials and Methods. During 2019-2020, we have performed a cross-sectional survey in the adult population of the Omsk region (n = 441, age 18-83 years). Questionnaires included an information regarding the food intake, nutritional status, and health status. In addition, we measured body mass index, waist circumference and waist-to-hip ratio. Among the parameters, we evaluated average daily consumption of energy, fats, cholesterol, saturated, monounsaturated, and polyunsaturated fatty acids, phospholipids, linoleic acid, alpha-linolenic acid, and arachidonic acid. In addition, we assessed the ratio of omega-6 to omega-3 fatty acids in the diet, specific weight of vegetable fats, and the energy quotas of individual nutrients.Results. In the population of Western Siberia, we found insufficient intake of alpha-linolenic acid (69.6 ± 2.2% population), arachidonic acid (55.3 ± 2.4%), polyunsaturated fatty acids (44.4 ± 2.4%), and phospholipids (37.6 ± 2.3%), as well as excessive consumption of cholesterol (74.1 ± 2.1%), total fats (61.9 ± 2.3%), saturated fatty acids (47.8 ± 2.4%), monounsaturated fatty acids (37.6 ± 2.3%), energy (34.7 ± 2.1%), and linoleic acid (31.1 ± 2.2%). In all groups of respondents, we registered high values of the omega-6/omega-3 ratio. The proportion of respondents with adequate consumption of energy and nutrients did not exceed 59.2 ± 2.3%.Conclusion. The diet of the adult population in Western Siberia was characterized by dysbalanced lipid consumption (more than 60% of the population). We documented an insufficient consumption of polyunsaturated fatty acids and phospholipids in combination with excessive consumption of products containing cholesterol, saturated fatty acids, monounsaturated fatty acids, and linoleic acid.